(untitled) (Marketing Journal, 2025)
In the context of strengthening the strategic partnership between the Republic of Uzbekistan and the People’s Republic of China, the development of mutual tourism exchange is becoming a key component of cultural and economic cooperation. The aim of this study is to identify effective mechanisms for encouraging tourist flows and improving service infrastructure. The methodology is based on the analysis of official statistics, cultural exchange programs, regulatory documents, and logistics strategies. The research highlights the following priorities: expansion of the visa-free regime, increase in direct flights, digitalization of tourism services, professional training, and promotion of Uzbekistan’s tourism brand in China. Special attention is given to the “Year of Uzbekistan Tourism in China” as a tool for strengthening humanitarian ties. Practical recommendations are formulated for institutional consolidation of tourism cooperation and sustainable development of bilateral tourist flows.